2019
DOI: 10.1088/1742-6596/1366/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection flow of Sodium Alginate based Casson nanofluid about a solid sphere in the presence of a magnetic field with constant surface heat flux

Abstract: In this paper, we examined a free convection flow of Sodium Alginate (SA) as a host Casson fluid with three different types of nanoparticles specifically, Silicon Dioxide (SiO2), Copper oxide (CuO), and Copper (Cu) on a solid sphere in the presence of magnetic field along with prescribed surface heat flux. The Keller-box method was carried out for solving the transformed governing partial differential equations. Numerical results for the local skin friction coefficient are obtained and compared with literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Khan et al. 34 modeled the MHD heat transfer features of Casson fluid with chemical reaction and Joule heating (for more details see literature 3537 ).…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al. 34 modeled the MHD heat transfer features of Casson fluid with chemical reaction and Joule heating (for more details see literature 3537 ).…”
Section: Introductionmentioning
confidence: 99%
“…( 2 = 1 = 0) are represent to a regular Newtonian fluid. Besides, to simplify the above problem equations, we get the following non-dimensional variables, as follows [9,10] = ( ̅ ) , = ( ̅ ) ,…”
Section: Tablementioning
confidence: 99%
“…(6) to Eq. (8), subject to the boundary conditions ( 9), we assume the following variables [9] = ( ) ( , ), = ( , )…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…In their examination of the magneto-3D flow of non-Newtonian Casson liquid with thermal radiation, Thumma et al [13] observed that raising the Casson parameter values considerably reduces the velocity curve. For more reading, see the following articles [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%